EXTRACTING THE ALKHLAKUL KARIMAH VALUE IN ZAPIN TRADITIONAL ART AS THE REINFORCEMENT TOWARD CURRICULUM 2013 - Ellya Roza (Fakultas Bahasa dan Seni Universitas Negeri Padang, 2014)
Zapin is one of the culture that derived from Arabic culture which was growing in the Indonesia through a process of Islamization. Zapin in Indonesia grow and develop accordance with the customs and conditions of local communities. Zapin is composed of three elements namely music, song and dance. Three elements are complementary each other and create harmony of movement and rhythm which are eyecatching and earcathing. In the Indonesia of the past, especially in the region of the Kingdom of Siak, Zapin is an palace art that is patented by the sultan for certain events such as welcoming guests and celebrations in the kingdom so that when Zapin displayed much rule that must be understood and practiced by zapiner, both musicians, singers and dancers. For example, not allowed to dance in pairs between men and women, wear clothes that are neat and cover the body as religion rule, polite, indicates a movement that glorifies and many other procedures. When reviewed and examined in depth the whole that rule, in essence teaches ethics and akhlakul karimah to the performers and audience of Zapin. Expiration of the kingdom in the Indonesia as the kingdom of Siak did not make Zapin faded, Zapin defended in the community because its content suitable with appoint teaching and attitude life of the Indonesia’s people who are prioritize the religiosity. It means the presence of Zapin as one of the traditional art form still exist for people now even the value contained in the Zapin never faded though modern art has become popular. Therefore, this paper tries to explore the existence of Zapin especially akhlakul karimah value contained in it, so Zapin become one of the traditional arts and empowering for the life of society and state even act as strengthening the curriculum in 2013 as the government declared today Kata kunci: Zapin, exploring, value, akhlakul karimah, curriculum 2013